INDONESIAN MIGRANT WORKERS (IMW) AND HUMAN TRAFFICKING: PERSPECTIVES FROM ISLAMIC AND HUMAN RIGHTS STANDPOINTS - Kusumawati, Mustika Prabaningrum (Universitas Syiah Kuala, 2024)
Indonesian migrant workers (IMW) serve as a stark representation of female poverty in Indonesia. Despite the constitutional guarantees outlined in Article 27 of the 1945 Constitution, which ensure employment opportunities both domestically and internationally, many IMW find themselves ensnared in the web of human trafficking. This article delves into this pressing issue through the dual lenses of Islamic teachings and human rights principles. Employing a normative legal research methodology with a statutory approach, a comparative analysis was conducted to evaluate the regulatory frameworks concerning IMW and human trafficking. Both Islam and human rights frameworks underscore the gravity of human trafficking, emphasizing the government's duty to prioritize domestic employment opportunities for women to safeguard their livelihoods. The eradication of human trafficking hinges on four key pillars: prevention, prosecution, protection, and partnership. Enhanced efforts are imperative to create suitable employment opportunities for IMW, particularly women, aligning with Islamic teachings and upholding global and national human rights standards for women's protection.